THE CREATIVE MARKETING STRATEGY IN DEVELOPING PANDAN WOVEN PRODUCTS IN THE MARKET AT MSMES “JAXEE” - Ismaya, Sakti Brata; Indrajaya, Titus; Widyasari, Lala; Tukiyat, Tukiyat; Supriyani, Mei (International Journal of Multidisciplinary Research and Literature, 2024)
The economic crisis caused by the COVID-19 pandemic at the beginning of 2020 has significantly impacted the micro, small and medium enterprise (MSME) sector in this country. In this context, this research examines the strategic efforts UMKM "JAXEE" Pandan Woven adopted to develop the market for their pandan woven products. Data collection techniques used in this research include documentation, interviews and observation. The collected data was then analyzed using content analysis methods (documentation research) and descriptive analysis. "JAXEE" Woven Pandan is an MSME that produces woven pandan souvenirs such as bags, fans, wallets, hats, sandals, key chains and other products with various color patterns. The importance of the latest innovations in pandan woven products and the development of fashion trends are the main focus of "JAXEE" to remain competitive in this industry. They are starting to pay attention to competitive aspects by following technological developments, utilizing social media, and having personal websites to increase visibility and customer relationships.